The real engines of Africa s economies - Lopes D'Almeida, Gisele (Technical Centre for Agricultural and Rural Cooperation, 2002)
The engine behind Africa s economic potential is the food processing sector, and it is of fundamental importance to strengthen it, give it breathing space and accord it its proper strategic role.When we set up the Interface network it was precisely...